Integrating Nutraceuticals into Diabetes Care: A Systematic Overview - Anil Kumar (Revista Electronica de Veterinaria, 2024)
The rising global incidence of diabetes requires novel strategies for its care. This review examines the crucial significance of nutraceuticals, herbs, and natural products as alternative therapies for diabetes. The limitations of synthetic pharmaceuticals in meeting various health requirements have resulted in a heightened dependence on nutraceuticals, defined as natural substances that enhance health and avert disease. This review examines diabetes mellitus, a multifaceted chronic illness, by investigating the historical origins of nutraceuticals from herbal medicine and their current applications in influencing biochemical and clinical outcomes. Case studies demonstrate the potential of nutraceuticals derived from bitter melon, black cumin, and cinnamon in diabetes control. The document classifies different nutraceuticals and their mechanisms, highlighting their effectiveness and reduced adverse effects in comparison to conventional pharmaceuticals. Furthermore, it addresses the recent increase in interest in nutraceuticals, emphasising their potential to enhance general health and diabetes. The final statements emphasise the necessity for regulatory frameworks and interdisciplinary collaboration to fully leverage the promise of nutraceuticals in improving health and quality of life.